Quaternary alloy core-shell quantum dot and preparation method thereof

By introducing a quad-alloy core-shell structure into quantum dots, using the CdZnSeS core, ZnxCd1-xSeyS1-y transition layer and ZnS shell, the interface defect problem caused by lattice mismatch in traditional quantum dots is solved, and high efficiency and stability are improved, while reducing the use of Cd elements and meeting environmental protection requirements.

CN119505908APending Publication Date: 2025-02-25INST OF NEW DISPLAY TECH HENAN ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411721934.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The traditional CdSe/ZnS core-shell structure quantum dots have increased interface defects due to lattice mismatch, making it difficult to improve fluorescent quantum yield and stability at the same time, and Cd elements have environmental risks.

Method used

CdZnSeS is used as the quantum dot core, and ZnxCd1-xSeyS1-y is introduced as the transition layer and ZnS is used as the shell to form a quad-alloy core-shell structure, reducing Cd elements and optimizing the interface structure between the core and shell.

Benefits of technology

It significantly reduces the use of Cd elements, reduces environmental risks and biological toxicity, improves the fluorescence efficiency and optical properties of quantum dots, and enhances its stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505908A_ABST
    Figure CN119505908A_ABST
Patent Text Reader

Abstract

The invention relates to a novel quaternary alloy core-shell quantum dot and a preparation method thereof, CdZnSeS is adopted as a core, a ZnxCd1-xSeyS1-y transition layer is introduced, and ZnS is adopted as a shell layer, so that a quaternary alloy core-shell structure is formed. A temperature increasing growth strategy is adopted, and parameters such as the proportion, the dropwise adding sequence, the dropwise adding speed and the reaction temperature of a precursor solution are controlled, so that the prepared quantum dot not only reduces the use of a Cd element, reduces the environmental risk and the biotoxicity, but also improves the stability and the fluorescence efficiency on the premise of ensuring the high yield. The specific preparation method comprises the following steps: respectively preparing precursor solutions containing a cadmium source, a zinc source, a sulfur source, a selenium source and the like, and reacting according to a specific sequence and conditions to form a quantum dot core, a transition layer and a shell layer. In addition, by adjusting the component proportion and controlling the temperature, adjustment of the light emitting wavelength of the quantum dots and optimization of the performance are achieved, the problem that the quantum dots are unstable in practical application is solved, and wide application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of quantum dot materials, and in particular to a quaternary alloy core-shell quantum dot and a preparation method thereof. Background Art

[0002] As a new type of nano fluorescent material, semiconductor quantum dots have shown broad application potential in many cutting-edge technology fields such as new display and lighting, solar cells and biomarkers due to their size-dependent multicolor luminescence characteristics, narrow fluorescence peak, high quantum yield and excellent photochemical stability. In particular, CdSe quantum dots can not only achieve the regulation of luminescence peak position in the blue-green light region by coating the outer layer with ZnS shell, but also improve the stability of quantum dots, which is of great significance for expanding its application scenarios.

[0003] However, traditional CdSe / ZnS core-shell structure quantum dots face a challenge: the lattice mismatch between CdSe and ZnS is as high as 12%. As the number of ZnS shells increases, this mismatch will lead to an increase in interface defects, thereby reducing the fluorescence quantum yield, making it difficult to simultaneously improve the fluorescence quantum yield and stability of the quantum dots. This limitation restricts the further development of CdSe / ZnS core-shell structure quantum dots in high-performance applications.

[0004] To overcome this problem, researchers explored multi-shell CdSe / Cd x Zn 1-x Se / ZnS gradient core-shell structure quantum dots are introduced by Cd x Zn 1-x Se gradient shell is used to reduce interface defects and thus improve quantum yield. Although this approach has been successful to a certain extent, new problems have also emerged. The ZnSe part in the gradient shell acts as a hot electron transfer path, making the quantum dots susceptible to photooxidation, thereby reducing their long-term stability. In addition, the large amount of Cd element in the shell is contrary to the EU's ban on toxic and hazardous chemicals in electronic products, limiting the application of such quantum dots in fields with strict environmental requirements.

[0005] Therefore, it is necessary to optimize the growth process of ultra-thick ZnS shells to achieve two major goals: first, by reducing the ZnSe shell and increasing the ZnS shell, the stability of quantum dots can be further improved while ensuring a high yield; second, the composition of quantum dots meets environmental requirements, especially reducing the use of Cd elements. Summary of the invention

[0006] The purpose of the present application is to provide a quaternary alloy core-shell quantum dot and a preparation method thereof, which can reduce the use of Cd elements and improve stability under the premise of ensuring high yield of quantum dots. The purpose of the present application is achieved through the following technical solutions. The quaternary alloy core-shell quantum dot includes a quantum dot core, a transition layer, and a shell layer; The quantum dot core is CdZnSeS quantum dot; The material of the shell layer is ZnS; The material of the transition layer is Zn x Cd 1-x Se y S 1-y , wherein 0<x≤1, 1>y≥0, and in the transition layer, in the direction from the quantum dot core to the shell layer, the value of x gradually increases and the value of y gradually decreases.

[0007] In one embodiment, the thickness of the shell layer is greater than the thickness of the transition layer.

[0008] In one embodiment, the average size of the quantum dot core is in the range of 7-8 nm.

[0009] In one embodiment, the size of the quaternary alloy core-shell quantum dots is greater than 18 nm.

[0010] In one embodiment, the Cd content in the quaternary alloy core-shell quantum dots is less than 1%.

[0011] In addition, the present application also provides a method for preparing quaternary alloy core-shell quantum dots, comprising: A first precursor solution, a second precursor solution, and a third precursor solution are prepared respectively, wherein the first precursor solution comprises a cadmium source, a zinc source, an organic ligand, and an organic solvent, the second precursor solution comprises a sulfur source, a selenium source, a long-chain carbene, and an organic solvent, and the third precursor solution comprises a zinc source, an organic ligand, and a long-chain carbene; injecting a second precursor solution into the first precursor solution to form a first quantum dot solution; adding alkane thiol to the third precursor solution to form a mixed precursor solution; Adding the mixed precursor solution dropwise into the first quantum dot solution; The temperature of the solution increased during the addition.

[0012] In one embodiment, the temperature is increased while the dripping rate is increased.

[0013] In one embodiment, the amount of the mixed precursor solution added per hour is less than 10% of the amount of the first quantum dot solution.

[0014] In one embodiment, the molar percentage of cadmium in the first precursor solution is greater than the molar percentage of zinc, and the molar percentage of sulfur in the second precursor solution is greater than the molar percentage of selenium.

[0015] In one embodiment, the second precursor solution is injected into the first precursor solution at a temperature less than 120°C, and the starting temperature of the dripping of the third precursor solution is in the range of 120°C-180°C.

[0016] In one embodiment, the temperature during the dropwise addition process is increased in a stepwise manner, with the highest temperature being less than 350°C.

[0017] In one embodiment, the temperature is increased by 25-60° C. every 2-6 hours in a stepwise manner.

[0018] In one embodiment, the amount of the third precursor solution added dropwise at each increased temperature is greater than the amount of the third precursor solution added dropwise at the previous temperature.

[0019] Compared with the prior art, this application has the following beneficial effects: This application uses CdZnSeS as the quantum dot core by introducing Zn x Cd 1-x Se y S 1-y As a transition layer, and ZnS as a shell layer, a unique quaternary alloy core-shell structure is formed. Among them, the content of Zn (x value) in the transition layer gradually increases, the content of Cd gradually decreases, while the content of Se (y value) gradually decreases, and the content of S gradually increases, forming a gradient alloy layer, reducing the Cd element, reducing environmental risks and biological toxicity, and also optimizing the interface structure between the core and the shell through the formation of the gradient alloy layer, which helps to reduce interface defects, thereby improving the fluorescence efficiency and optical properties of quantum dots, and improving the stability of quantum dots.

[0020] In the preparation process, a temperature-increasing growth strategy is adopted, and the temperature of the solution is gradually increased when the mixed precursor solution is added dropwise, while the dropping speed and the amount of addition are controlled to ensure the uniform growth of the shell. By increasing the temperature, the core-shell interface stress can be effectively reduced to avoid structural defects caused by too fast temperature changes. At the same time, extending the reaction time helps the full growth of the ZnS shell, and the fluorescence quantum yield and the thickness of the ZnS shell are increased at the same time. In the preparation process, the parameters such as the ratio, the order of addition, the dropping speed and the reaction temperature of each precursor solution are strictly controlled to ensure the consistency of the size, shape and performance of the quantum dots. Through fine process control, the accurate regulation of the average size of the quantum dot core is achieved. The quaternary alloy core-shell quantum dots and preparation methods provided in the present application, through structural design and process control, achieve the beneficial effects of improving stability and fluorescence efficiency under the premise of ensuring the high yield of quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a schematic diagram of the structure of the quaternary alloy core-shell quantum dots in the embodiment of the present application; Figure 2 It is a TEM image of the quaternary alloy core-shell quantum dots in the example of the present application.

[0022] Explanation of reference numerals: 100, quantum dot core; 200, transition layer; 300, shell layer. DETAILED DESCRIPTION

[0023] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0024] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.

[0025] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0026] Traditional CdSe / ZnS core-shell quantum dots face problems such as lattice mismatch, increased interface defects, decreased quantum yield, and insufficient stability, which limit their further development and application. In order to overcome these challenges, researchers are constantly exploring new quantum dot structures and preparation methods. This application will introduce a new type of quaternary alloy core-shell quantum dot and its preparation method in detail. The quantum dot uses CdZnSeS as the quantum dot core 100, and introduces Zn x Cd 1-x Se y S 1-y As the transition layer 200, and ZnS as the shell layer 300, a unique quaternary alloy core-shell structure is formed. During the preparation process, a temperature-increasing growth strategy is adopted to strictly control the ratio of each precursor solution, the order of addition, the speed of addition, the reaction temperature and other parameters to ensure the excellent performance of the quantum dots. The quaternary alloy core-shell quantum dots prepared by this method not only significantly reduce the use of Cd elements, reduce environmental risks and biological toxicity, but also achieve the premise of ensuring high yield of quantum dots, improve stability and fluorescence efficiency. Next, the specific structure and preparation method of the quaternary alloy core-shell quantum dots will be described in detail. Please refer to Figure 1 to Figure 2 The quaternary alloy core-shell quantum dot in a preferred embodiment of the present application comprises a quantum dot core 100, a transition layer 200, and a shell layer 300. The quantum dot core 100 is a CdZnSeS quantum dot, the shell layer 300 is made of ZnS, and the transition layer 200 is made of Zn x Cd 1-x Se y S 1-y, wherein 0<x≤1, 1>y≥0, in the transition layer, in the direction from the quantum dot core to the shell layer, the value of x gradually increases, and the value of y gradually decreases. The quantum dot core 100 is first made into quantum dots using a precursor including cadmium and zinc and a precursor including sulfur and selenium. The luminescent wavelength of the quantum dot can be adjusted by components as needed. According to application requirements, the preferred emission wavelength is 500-580nm, and 540nm is further preferred. The material composition at the starting position where the transition layer 200 contacts the quantum dot is the same as the material composition of the quantum dot. In the entire quaternary alloy core-shell quantum dot of the present application, the cadmium element in the quantum dot core 100 can be reduced relative to the use of CdSe, and by further gradually reducing the content of Cd and Se in the transition layer 200, the composition is converted to ZnS, and finally a shell layer 300 composed of ZnS is formed. It should be noted that the "gradually decreasing" or "gradually increasing" here refers to a trend of decreasing or increasing, and is not limited to completely linear changes in the relevant components. The step-wise decrease or increase of the components is also within the meaning of "gradually decreasing" or "gradually increasing" here, and the trend of decreasing or increasing is not further limited. By introducing the transition layer 200, the lattice mismatch problem between the quantum dot core 100 and the shell 300 is effectively alleviated, the structural stability of the quantum dot is enhanced, and its service life is extended. The gradual composition design of the transition layer 200 reduces interface defects and improves the luminous efficiency and quantum yield of the quantum dot.

[0027] Specifically, the thickness of the shell 300 is greater than the thickness of the transition layer 200. This design can further optimize the stability of the quantum dot and its resistance to the external environment. As the outermost layer of the quantum dot, the shell 300 is responsible for protecting the internal quantum dot core 100 from interference from the external environment. Increasing the thickness of the shell 300 can improve the chemical stability and physical durability of the quantum dot and extend its service life in practical applications. At the same time, the thicker shell 300 can also more effectively isolate the internal Cd element and prevent it from leaking outward, thereby meeting the requirements for the Cd element from an environmental perspective. As a bridge between the quantum dot core 100 and the shell 300, the transition layer 200 plays a key role in alleviating lattice mismatch, reducing interface defects, and improving the overall performance of quantum dots. However, if the transition layer 200 is too thick, it may increase the overall size of the quantum dots and affect their applicability in certain specific applications. Therefore, under the premise of ensuring that the transition layer 200 can effectively perform its function, controlling its thickness within a certain range so that the thickness of the shell 300 is greater than that of the transition layer 200 becomes a reasonable choice.

[0028] Specifically, the average size of the quantum dot core 100 is in the range of 7-8nm. When the size of the quantum dot core 100 is reduced to the nanometer level, the quantum confinement effect will be exhibited, that is, the electrons and holes are confined in a very small space, resulting in changes in the energy band structure, so that the quantum dots have unique luminescence properties. However, if the size of the quantum dot core 100 is too small, it may lead to a decrease in luminescence efficiency because the recombination rate of electrons and holes may be limited. If the size of the quantum dot core 100 is too large, it may also cause the stability of the quantum dot to decrease. Controlling the average size of the quantum dot core 100 within the range of 7-8nm can achieve the best balance between luminescence efficiency and stability.

[0029] The quantum dots provided in the present application achieve large size and high quantum yield at the same time by forming a core-shell structure. Specifically, the size of the quaternary alloy core-shell quantum dots is greater than 18nm. Furthermore, the size of the quaternary alloy core-shell quantum dots is greater than 20nm, which are large-sized core-shell quantum dots. Prior to the present application, there were no large-sized and high-quantum-yield blue-green quantum dots in the prior art. The technical solution of the present application can prepare large-sized core-shell quantum dots in a controllable manner, and can meet the requirements for quantum dots to be large in size, uniform in size and stable in performance.

[0030] Since the core-shell quantum dots of the present application have a thicker ZnS shell layer, the Cd content in the quaternary alloy core-shell quantum dots of the present application is less than 1%, achieving a low Cd content while ensuring high quantum yield and stability. In addition, the thicker ZnS shell layer can also ensure that the Cd element does not leak, which can ensure stable structure and performance and meet environmental protection requirements. Further, the Cd content is preferably less than 0.1%.

[0031] In addition, the present application also provides a method for preparing quaternary alloy core-shell quantum dots, comprising: A first precursor solution, a second precursor solution, and a third precursor solution are prepared respectively, wherein the first precursor solution comprises a cadmium source, a zinc source, an organic ligand, and an organic solvent, the second precursor comprises a sulfur source, a selenium source, a long-chain carbene, and an organic solvent, and the third precursor solution comprises a zinc source, an organic ligand, and a long-chain carbene; in the process of forming the precursor solution, an appropriate ratio of each component is selected, and it can be known that the organic ligand and the organic solvent are in excess, and the relative contents of the cadmium source, the zinc source, the selenium source, and the sulfur source are added according to the chemical composition. This application does not make further details on the specific cadmium source, the zinc source, the organic ligand, and the organic solvent. One step is limited, as long as the materials that can provide the relevant elements for preparing the quaternary alloy core-shell quantum dots can be included, for example, cadmium sources include cadmium oxide, cadmium chloride, cadmium oxalate, cadmium acetate, cadmium carbonate, cadmium powder, cadmium stearate, cadmium fluoride, cadmium iodide, cadmium bromide, cadmium perchlorate, cadmium phosphide, cadmium nitrate, cadmium sulfate, etc., and the cadmium source in this application is preferably cadmium oxide, and the zinc source includes zinc oxide, zinc chloride, zinc acetate, etc., and the zinc source in this application is preferably zinc oxide, and the organic ligand selects the organic ligand commonly used in the preparation process of nanoparticles, such as fatty acids and fatty amines with a carbon number greater than 8, and the organic ligand in this application is preferably oleic acid. The organic solvent selects a commonly used organic solvent, such as paraffin oil, tetradecane, hexadecane, octadecane, etc., and the organic solvent of this application is preferably paraffin oil. Long-chain carbenes can select hexadecene and octadecene, preferably octadecene.

[0032] The second precursor solution is injected into the first precursor solution to form a first quantum dot solution. In this step, the second precursor solution needs to be quickly added to the first precursor solution, and the quantum dot core 100 is formed by the second precursor solution and the first precursor solution. Since the first precursor solution includes a cadmium source, a zinc source, an organic ligand and an organic solvent, and the second precursor includes a sulfur source, a selenium source, a long-chain carbene and an organic solvent, this process can form a quantum dot core 100 including Cd, Zn, Se, and S, and the quantum dot core 100 exists in the solution. In addition, since the transition layer 200 and the shell layer 300 need to be grown, the quantum dot core 100 is not purified and is retained in the solution.

[0033] Alkane thiol is added to the third precursor solution to form a mixed precursor solution. By adding alkane thiol as the sulfur element in the mixed precursor solution, the mixed precursor solution at this time includes both a zinc source and a sulfur source, and the introduction method of the sulfur source is different from that of the sulfur source in the second precursor solution.

[0034] The mixed precursor solution is added dropwise to the first quantum dot solution, and the transition layer 200 and the shell layer 300 are slowly grown by dropping. The temperature of the solution is increased during the dropping process, and the temperature increase here includes slowly increasing the temperature linearly and stepwise. In this process, since the mixed precursor solution is added by dropping, the components in the solution will undergo slight changes, and the change in temperature will break the balance of the components in the first quantum dot solution that have not formed quantum dots, so that further growth can be achieved on the surface of the quantum dot core 100, and since it is a dropping method, the change in the components is slow, and the components do not mutate, so the growth rate on the surface of the quantum dot core 100 is controllable, which can minimize interface defects.

[0035] Specifically, the temperature is increased while the dripping speed is increased. In order to optimize the reaction efficiency and product quality, the dripping speed of the reactants is increased while the operating temperature is increased. This approach is based on the principle of chemical reaction kinetics, that is, the increase in temperature can increase the average kinetic energy of molecules, causing them to collide more frequently and more violently, thereby promoting the reaction. At the same time, increasing the dripping speed means that the reactants can enter the reaction system more quickly, increasing the number of effective contacts of the reactants per unit time, and further accelerating the reaction rate.

[0036] However, in order to control the reaction speed and reduce interface defects as much as possible, the amount of the mixed precursor solution added per hour is less than 10% of the amount of the first quantum dot solution. Slowly adding the mixed precursor solution helps to form a uniform layer on the surface of the quantum dots, which can reduce the differences between different quantum dot cores 100 and improve the uniformity of the product.

[0037] Specifically, the molar percentage of cadmium in the first precursor solution is greater than the molar percentage of zinc, and the molar percentage of sulfur in the second precursor solution is greater than the molar percentage of selenium. By adjusting the molar percentages of related elements, the components are regulated. Specifically, in the solution of the present application, the molar percentage of sulfur in the second precursor solution is greater than the molar percentage of selenium. When forming the quantum dot core 100, by using more cadmium elements and combining the reaction temperature, the selenium element can be consumed first, so that the sulfur element present in the solution has a higher proportion. When zinc elements are added later, the proportions of cadmium elements and selenium elements can be reduced more quickly, and the proportions of zinc elements and sulfur elements can be increased, so that the transition layer 200 can meet the requirements of reducing interface defects while controlling the relative thickness of the transition layer 200.

[0038] Specifically, the second precursor solution is injected into the first precursor solution at a temperature less than 120° C., and the starting temperature of the third precursor solution is within the range of 120° C.-180° C. The starting temperature determines the quality of the quantum dot core 100 and is conducive to the formation of CdZnSeS quantum dots. It is found through experiments that the above starting temperature range can better form CdZnSeS quantum dots and is conducive to the controllable temperature increase growth process of the subsequent transition layer 200.

[0039] In order to optimize the reaction conditions, improve the product quality and reaction efficiency, the temperature during the drop addition process is increased by a step-by-step temperature increase method, and the maximum temperature is less than 350°C. A relatively low temperature is set at the beginning of the drop addition, and then the temperature is gradually and steadily increased to a preset maximum temperature according to the predetermined step-by-step temperature increase program, and this maximum temperature is strictly controlled below 350°C. This temperature control method not only ensures the smooth progress of the reaction process, but also helps to gradually activate the reactant molecules so that they react at a more suitable speed at different temperature stages. By accurately controlling the temperature increase rate and the maximum temperature, the crystal growth process can be optimized and crystal defects can be reduced. This step also fully considers the thermal stability of the reactants, intermediates and products, and avoids possible side reactions. In order to further ensure the stability and uniformity of the product, the temperature is increased by 25-60°C every 2-6 hours in the step-by-step temperature increase method.

[0040] In order to accelerate the formation of the shell layer 300, the amount of the third precursor solution added at each increased temperature is greater than the amount of the third precursor solution added at the previous temperature. In this way, there is almost no cadmium element and selenium element in the subsequently formed shell layer 300, and the transition from the transition layer 200 to the shell layer 300 is naturally completed, and it helps to form a shell layer 300 with a relatively larger thickness.

Claims

1. A quaternary alloy core-shell quantum dot, characterized in that: It includes quantum dot core, transition layer and shell layer; The quantum dot core is CdZnSeS quantum dot; The material of the shell layer is ZnS; The material of the transition layer is Zn x Cd 1-x Se y S 1-y ; Among them, 0<x≤1, 1>y≥0, in the transition layer, in the direction from the quantum dot core to the shell layer, the value of x gradually increases, and the value of y gradually decreases.

2. The quaternary alloy core-shell quantum dot according to claim 1, characterized in that: The thickness of the shell layer is greater than the thickness of the transition layer.

3. The quaternary alloy core-shell quantum dot according to claim 1, characterized in that: The average size of the quantum dot core is in the range of 7-8nm.

4. The quaternary alloy core-shell quantum dot according to claim 3, characterized in that: The size of the quaternary alloy core-shell quantum dots is greater than 18 nm.

5. The quaternary alloy core-shell quantum dot according to claim 1, characterized in that: The Cd content in the quaternary alloy core-shell quantum dots is less than 1%.

6. A method for preparing quaternary alloy core-shell quantum dots, characterized in that: include: A first precursor solution, a second precursor solution, and a third precursor solution are prepared respectively, wherein the first precursor solution comprises a cadmium source, a zinc source, an organic ligand, and an organic solvent, the second precursor solution comprises a sulfur source, a selenium source, a long-chain carbene, and an organic solvent, and the third precursor solution comprises a zinc source, an organic ligand, and a long-chain carbene; injecting a second precursor solution into the first precursor solution to form a first quantum dot solution; adding alkane thiol to the third precursor solution to form a mixed precursor solution; Adding the mixed precursor solution dropwise into the first quantum dot solution; The temperature of the solution increased during the addition.

7. The method for preparing quaternary alloy core-shell quantum dots according to claim 6, characterized in that: Increase the temperature and increase the rate of addition.

8. The method for preparing quaternary alloy core-shell quantum dots according to claim 6 or 7, characterized in that: The amount of the mixed precursor solution added dropwise per hour is less than 10% of the amount of the first quantum dot solution.

9. The method for preparing quaternary alloy core-shell quantum dots according to claim 6, characterized in that: The molar percentage of cadmium in the first precursor solution is greater than the molar percentage of zinc, and the molar percentage of sulfur in the second precursor solution is greater than the molar percentage of selenium.

10. The method for preparing quaternary alloy core-shell quantum dots according to claim 6, characterized in that: At a temperature less than 120°C, the second precursor solution is injected into the first precursor solution. The starting temperature of the third precursor solution is within the range of 120°C-180°C. The temperature is increased during the addition by a step-by-step temperature increase. The maximum temperature is less than 350°C. The temperature is increased by 25-60°C every 2-6 hours in the step-by-step temperature increase. The amount of the third precursor solution added at each increased temperature is greater than the amount of the third precursor solution added at the previous temperature.

Citation Information

Patent Citations

  • Non-scintillation core-shell structure quantum dot and preparation method thereof

    CN108048073A

  • Core-shell quantum dot as well as preparation method and application thereof

    CN118006335A